Driving Circularity through Reverse Logistics: Policies, Technologies, and Consumer Dynamics - Setiadi (Yayasan Sinergi Kawula Muda, 2024)
Reverse logistics plays a critical role in enabling circular economy models by facilitating resource recovery, reducing environmental impact, and promoting sustainable production-consumption cycles. This narrative review aims to synthesize current literature on reverse logistics in the context of circular economy strategies, with a particular focus on consumer participation, regulatory frameworks, and technological innovation. Using a narrative methodology, the review draws upon peer-reviewed studies sourced from Scopus and Web of Science, covering empirical and conceptual contributions from 2000 to 2024. The findings indicate that consumer behavior, influenced by environmental awareness, trust, and financial incentives, remains a crucial enabler of reverse logistics. Regulatory interventions such as Extended Producer Responsibility (EPR) and tax incentives have proven effective but often encounter challenges in implementation due to fragmented governance and limited inter-agency coordination. Technological advancements, including artificial intelligence, Internet of Things (IoT), and blockchain, have enhanced supply chain transparency and efficiency, although digital inequality poses challenges in developing regions. The discussion highlights the influence of systemic barriers, such as rigid bureaucracies and cultural resistance, which require adaptive policy solutions and inclusive governance. To address existing gaps, future research must integrate interdisciplinary approaches, especially in underrepresented regions. Ultimately, aligning technological, policy, and social dimensions will be essential to unlocking the full potential of reverse logistics within circular economy frameworks.